2004
DOI: 10.1634/stemcells.22-1-65
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Myeloma Cells Involves SDF‐1/CXCR4 Signaling and Downregulation of VLA‐4

Abstract: Adhesion molecules and stromal cell-derived factor-1 (SDF-1)/CXCR4 signaling play key roles in homing and mobilization of hematopoietic stem cells (HSC). Active signaling through SDF-1/CXCR4 and upregulation of adhesion molecules are required for homing, whereas downregulation of adhesion molecules and disruption of SDF-1/CXCR4 signaling are required for mobilization of HSC. We studied the surface expression of CXCR4 very late activation antigen (VLA)-4 and VLA-5 on myeloma cells mobilized with cyclophosphamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…Then, such frequency is far from those of the French and of the Spanish population (0.329 and 0.359) and more closer to our result in Tunisian population [Yair Gazitt & Cagla Akai, 2004].…”
Section: Discussionsupporting
confidence: 83%
“…Then, such frequency is far from those of the French and of the Spanish population (0.329 and 0.359) and more closer to our result in Tunisian population [Yair Gazitt & Cagla Akai, 2004].…”
Section: Discussionsupporting
confidence: 83%
“…This function of SDF-1/CXCR4 axis has been confirmed in several tumors such as lung cancer, prostate carcinoma and breast cancer. 14,15,17,[43][44][45][46][47][48][49][50][51] Our previous report found that the CXCR4 expression in NPC lesions was positively correlated with tumor distant metastasis and poor survive. 52 In this study, in 56 NPC lesions 30% (17/56) had a high expression level of CXCR4, and the CXCR4 was expressed in the cellular nucleus or cytoplasm and membrane of NPC tumor cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that the SDF-1/CXCR4 axis play an important and unique role not only in the egress of haematopoietic stem/progenitor cells from bone marrow into peripheral blood during mobilization and organogenesis, but also for tumor metastasis and development. [14][15][16][17][18][19][20] It is becoming clear, however, that neoplastic cells might evade the adaptive immune system by altering the expressions of specific molecules on the target cells. MHC class I is responsible for direct presentation of tumor antigen peptides to cytotoxic T lymphocytes (CTLs) ( via peptide-MHC complexes, while HLA class II can endogenously derive peptides to CD4+ T cells.…”
mentioning
confidence: 99%
“…These actions include the mobilization and adhesion of multiple myeloma plasma cells to stroma (11), the proliferation and migration of multiple myeloma plasma cells (12), the recruitment of osteoclasts to the bone marrow (13), and, most recently, the enhancement of osteoclastic bone resorption (14,15). In this study, we determined whether multiple myeloma plasma cell -derived SDF-1a could stimulate angiogenesis in vitro and examined whether SDF-1a promotes angiogenesis in multiple myeloma patients.…”
mentioning
confidence: 99%